Exploring al-Manhaj al-Qur’ani (The Qur’anic methodology) in dealing with other religions: an exegetical analysis of selected verses - Shehu, Fatmir Mehdi; Zejno, Bukuri (IIUM Press, 2020)
This paper seeks to explore al-Manhaj al-Qur’ani (the Qur’anic methodology) in dealing with other religions. It uses exegetical analysis of selected Qur’anic verses related to other religious communities. The contents of the selected verses are thematically analyzed, and in doing so, ways of how to deal with followers of other religions are duly identified, illustrated and analyzed. The significance of this research stands on its attempt to provide new insights about al-Manhaj al-Qur’ani in dealing with adherents of other religions. Al-Qur’an – the Divine Source of Knowledge and the selected Qur’anic methods, namely: descriptive; objective; analytical; critical; comparative; argumentative; and travelogue are discussed in this study. This research paper concludes that al-Manhaj al-Qur’ani in dealing with other religions, their main teachings and communities is very significant and relevant to contemporary Muslim scholarship in comparative religion.